ANALISIS EFEKTIFITAS MEDIA SOSIAL INSTAGRAM SEBAGAI SARANA PROMOSI PADA KANTOR POS INDONESIA CABANG SINTANG - Damiana, Damiana (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
This research is motivated by the phenomenon of social media use, particularly Instagram, as a promotional tool and the public's awareness of the services available at the Indonesian Post Office, Sintang Branch. This study aims to determine, describe, and analyze the effectiveness of Instagram as a promotional tool. The scope of this research is social media (Instagram), Instagram social media promotion, and the effectiveness of Instagram. This research is descriptive, using qualitative methods with a phenomenological approach. The subjects were the Instagram admin of the Indonesian Post Office, the content creators of the Indonesian Post Office, and the followers of the Indonesian Post Office's Instagram account. Data collection techniques included interviews, observation, and documentation studies. Data analysis techniques included data reduction, data presentation, and conclusions. The results of this study indicate that the Indonesian Post Office, Sintang Branch, has utilized Instagram as a promotional tool. Instagram is an effective social media platform for promotion due to its widespread use among various groups. However, the use of Instagram as a promotional tool by the Indonesian Post Office, Sintang Branch, has been ineffective. This is due to the lack of a dedicated team responsible for digital marketing. This absence of a dedicated team has prevented the Post Office from implementing promotions optimally. They are unable to maintain consistency in posting and creating content regularly due to the various other tasks that are part of their daily responsibilities. Consistent posting and creating quality content are key to attracting a wider audience. Without a dedicated team, promotional efforts are suboptimal and less able to increase public understanding of the services provided by the Post Office. In addition to using Instagram as a promotional tool, the Sintang branch of the Indonesian Post Office also conducts real-world promotions or field promotions by implementing a proactive and personalized approach to reach potential customers. Based on the research findings, it is recommended that the Sintang branch of the Indonesian Post Office establish a dedicated digital marketing team focused on promotions. With this dedicated team, the Post Office can develop a more structured and consistent promotional strategy. This will facilitate more effective dissemination of information to the public, thereby increasing their understanding of the services available at the Sintang branch.